Efficient voltammetric platform combining a molecularly imprinted polymer and silver-nanoparticle-decorated black phosphorus nanosheets for selective determination of Gatifloxacin - Jingtao Wu; Yonghui Xia; Tianyu Wang; Yafeng Zhang; Guangli Li (Food Chemistry: X)
An ultrasensitive and selective voltammetric platform combined a molecularly imprinted poly(pyrrole) membrane with Ag-nanoparticle-functionalized black phosphorus nanosheets (MIP/BPNS-AgNPs) was developed for trace GAT detection. The physicochemical properties of the MIP/BPNS-AgNPs were studied by various spectroscopic and electrochemical techniques. BPNS-AgNPs improved the ambient stability and electrochemical activity of the BPNS and possessed a large surface area for accommodating abundant templates to produce specific imprinted sites. The resulting MIP/BPNS-AgNP-modified glassy carbon electrode (GCE) greatly enhanced voltammetric responses for GAT. The MIP/BPNS-AgNP/GCE exhibited admirable GAT determination performance, with two linear responses (0.001–1 and 1–50 μM), high sensitivity (9.965 and 0.5378 μA μM−1), and a low detection limit of 0.2 nM. In addition, the MIP electrode could selectively detect GAT in complex matrices and retain roust responses for a month. The applicability of MIP/BPNS-AgNP/GCE toward the detection of GAT in pharmaceutical formulations, milk, and human serum was verified with satisfactory results.